Banking and Fiscal Unions in the EU: What is More Relevant? - A. N. Tsibulina (Vestnik MGIMO-Universiteta, 2014)
The article deals with financial system structures in the eurozone member states, linkages between banking sectors and fiscal solvency of states and EU initiatives towards improving frameworks to prevent and if necessary to deal with crises in the future. The global economic and financial crisis has revealed a close interrelation between banks problems and sovereigns in the EU. The instruments which were used by national governments in order to save systemically important banks forced the EU to revise approaches to bank supervision and establish new mechanisms for banks' restructuring. At the same time sovereign debt crises in a number of member-states, on the one hand, showed lack of an effective EU-wide system of control over a fiscal discipline and, on the other hand raised questions about lack of any system of fiscal transfers to countries hit by a negative shock. The New Banking and Fiscal unions have been designed to withshand those challenges. The author analyses problems which might be solved with the help of the new instruments established within theabove mentioned unions. At the same time far from all initiatives aimed at achieving greater fiscal consolidation might turn out to be effective when dealing with systemic problems in times of a crisis.